Model Perencanaan Material MRP-JIT untuk Meminimalkan Risiko Keterlambatan dalam Produksi Panel SDP - Mohamad Fatur Ramdan; Siti Rahayu; Rini Siskayanti (UNISTEK, 2026)
PT Kimindo Jaya Indonesia is an electrical panel manufacturing company that applies a Make-to-Order production system. One of the main problems faced by the company is material delay in Sub Distribution Panel (SDP) production, because several critical components are not available according to the assembly schedule. This study aims to develop an integrated Material Requirement Planning and Just-in-Time (MRP-JIT) material planning model to minimize delay risk in SDP panel production. This research used a descriptive quantitative approach with production data from January to June 2025. The data included production quantity, Bill of Materials, initial inventory, safety stock, scheduled receipts, supplier lead time, assembly schedule, and historical material delay data. Data processing was conducted through gross requirement calculation, net requirement calculation, Lot-for-Lot sizing, planned order receipt, planned order release, and JIT-based material arrival synchronization. The actual condition showed 10 material delay cases, with a total delay of 43 days and an average delay of 4.3 days per case. The proposed model scheduled material orders based on supplier lead time and targeted material arrivals one to two days before assembly. The results indicate that the MRP-JIT model can support the shift from reactive purchasing to preventive material planning.